Tissue culture in disease elimination and micropropagation - Ng, S.Y.C.; Thottappilly, G.; Rossel, H.W. (1992)
Meristem-tip culture is commonly used to eliminate viruses from plants. The fact that some viruses are more difficult to eliminate than others has led to the use of thermotherapy and chemotheraphy, along with meristem-tip culture, to increase the efficacy of disease elimination. Tissue culture material is considered to be the most suitable form to international exchange of vegetative plant material and is accepted by quarantine authorities. Micropropagation is used in both research institutions and commercial companies to produce large quantities of high quality planting materials. It is applied to vegetatively propagated crops, those crop species that are difficult to multiply, and new hybrids. It is achieved through the induction of axillary shoot formation, direct and indirect adventitious shoot formation, somatic embryogenesis, and storage organ formation. This paper describes tissue culture techniques used for both disease elimination and micropropagation and discusses the advantages and disadvantages of different techniques